VPAC1 receptors for imaging breast cancer: a feasibility study - Thakur, Mathew L (J Nucl Med, 2013)
VPAC1 encodes G-protein coupled receptors expressed on all breast cancer (BC) cells at the onset of the disease, but not on benign lesions. Our extensive preclinical studies, have shown that Cu-64-TP3805 has a high affinity for VPAC1, is stable in vivo and has the ability to distinguish spontaneously grown malignant BC masses from benign lesions. Our long term goal is to develop Cu-64-TP3805 as an agent to perform in vivo histology, to distinguish malignant lesions from benign masses noninvasively and thereby avoid patient morbidity and excess economic costs of benign biopsies. METHOD: F-18-FDG obtained commercially served as a control. Cu-64-TP3805 was prepared by using a sterile kit containing 20 µg TP3805. Radiochemical purity and sterility were examined. Nineteen consenting females with histologically proved BC were given 370 MBq F-18-FDG. One hr later, 6 of these patients were imaged with PET/CT and 13 with PEM (positron emission mammography). Two to seven days later, 6 PET/CT patients received 111±10% MBq (n=2), 127±10% MBq (n=2) or 148±10% MBq (n=2) Cu-64-TP3805 and imaged 2 hr and 4 hrs later. Thirteen PEM patients received 148±10% MBq Cu-64-TP3805, and imaged at 15 min, 1 hr, 2 hr and 4 hr post injection. For PET/CT patients SUV was calculated and for PEM patients PUV/BGV (PEM uptake value/background value) determined. Tumor volume was also calculated. RESULTS: Radiochemical purity of Cu-64-TP3805 was 97±2% and Specific Activity was 44.4 GBq (1.2 Ci)/µ mol. In 19 patients a total of 24 lesions were imaged (15 IDC, 1 high grade mammary carcinoma, 3 lobular carcinoma, 1 invasive papilloma and 4 sentinel lymph nodes). All lesions were unequivocally detected by Cu-64-TP3805 as well as by F-18-FDG. The average tumor volume with Cu-64-TP3805 as determined by PET/CT was 90.6±16% of that of F-18-FDG PET/CT and SUV values were 92±26.4% of that of F-18-FDG. For PEM, the tumor volume with Cu-64-TP3805 was 113±37% of that of F-18-FDG and PUV/BGV ratio was 97.7±24.5% of that of F-18-FDG. CONCLUSION: Cu-64-TP3805 is worthy of further investigation in patients requiring biopsy of suspicious imaging findings, to further evaluate its ability to distinguish malignant lesions from benign masses, noninvasively.